Sacre bleu : a comedy d'art - Moore, Christopher, 1957- (William Morrow, 2012)
"From repeat New York Times bestselling author Christopher Moore comes a love story, the portrait of a young artist, the portrait of the young artist's myterious girlfriend, a thriller, and a comedy -- all about the color blue"--